Analisis Determinan Pertumbuhan Ekonomi Di Indonesia Tahun 2000-2021 - Ayu Kania Azzahra, Akalili; Soebagyo, Daryono (GEMA EKONOMI, 2023)
This research aims to determine the effect of foreign debt, foreign investment, interest rates, and exchange rates on economic growth in Indonesia in the 2000-2021 period. The data used in this research is a time series using a multiple regression analysis tool model with the Partial Adjustment Model (PAM) approach. The results obtained in this research are that the foreign debt variable has a positive and significant effect on economic growth in Indonesia. The foreign investment variable has a significant negative effect on economic growth in Indonesia in the 2000-2021 period. Meanwhile, the interest rate and exchange rate variables did not yield significant results for economic growth in the 2000-2021 period.